Economic trade-offs between milk and meat production under various supplementation levels in Botswana - Konandreas, P.A.; Anderson, F.M.; Trail, J.C.M. (International Livestock Centre for Africa, 1983)
Describes a dynamic & stochastic simulation model, specifying its driving variables & validating it for production conditions in a study area in Botswana. Compares the simulated performance of Tswana & Simmental x Tswana cattle, analysing economic trade-offs between milk & meat production under various supplementation levels & milking policies.